Analysis of An SEI1I2QRV S Epidemic Infectious Disease Model with Multiple Infection Stages and Virus - Agrawal, Smriti; Mishra, Nimisha; Dhar, Joydip (Journal of Neonatal Surgery, 2025)
In this study, we propose an SEI1I2QRV Smodel for epidemic infec- tious diseases, which simulates the process of virus transmission. The model demonstrates how the virus impacts individuals who are infected. It is a well-established fact that the spread of infectious diseases can contribute to the proliferation of the virus within a susceptible population. One method of managing infectious diseases is to raise the virus-related fatality rate. In order to explain the virus’s growth and decline rates in the susceptible pop- ulation, the suggested model will be examined. We investigate the dynamic behaviour inside the model’s framework. It is shown that the model has two equilibrium points: a disease-free equilibrium (DFE) and an endemic equi- librium (EE). According to our results, the basic reproduction number, or R0, has a major impact on the model’s dynamics. When R0 < 1, the DFE is asymptotically stable both globally and locally under specific conditions. On the other hand, if R0 > 1, the internal equilibrium is asymptotically stable both globally and locally. Finally, we evaluate our analytical results by numerical simulations utilizing biologically relevant parameter values